Kidney Response to Heart Failure: Proteomic Analysis of Cardiorenal Syndrome - Vojtech Melenovsky; Ludek Cervenka; Ondrej Viklicky; Janka Franekova; Tereza Havlenova; Matej Behounek; Martin Chmel; Jiri Petrak (Karger Publishers, 2018)
Background/Aims: Chronic heart failure (HF) disrupts normal kidney function and leads to cardiorenal syndrome that further promotes HF progression. To identify potential participants in HF-related injury, we analyzed kidney proteome in an established HF model. Methods: HF was induced by chronic volume overload in male HanSD rats using aorto-caval fistula. After 21 weeks, cardiac and renal functions (in-situ kidney study) and renal proteomics were studied in sham-operated (controls) and HF rats, using iTRAQ labeling and LC-MS with Orbitrap Fusion, leading to identification and quantification of almost 4000 proteins. Results: Compared to controls, HF rats had cardiac hypertrophy, systemic and pulmonary congestion. Kidneys of HF rats had reduced renal blood flow, sodium excretion and urine production. While glomerular filtration rate, serum cystatin C and creatinine were still normal compared to controls, HF kidneys showed albuminuria and markedly increased tissue angiotensin-II levels (5-fold). HF kidneys (versus controls) displayed differential expression (˃1.5-fold) of 67 proteins. The most upregulated were angiotensin-converting enzyme (ACE, ˃20-fold), advanced glycosylation product-specific receptor (RAGE, 14-fold), periostin (6.8-fold), caveolin-1 (4.5-fold) and other proteins implicated in endothelial function (vWF, cavins 1-3, T-kininogen 2), proinflammatory ECM activation (MFAP4, collagen-VI, galectin-3, FHL-1, calponin) and proteins involved in glomerular filtration membrane integrity (CLIC5, ZO-1). Carboxylesterase-1D (CES1D), an enzyme that converts ACE inhibitors or sacubitril into active drugs, was also upregulated in HF kidneys. Conclusion: Chronic HF leads to latent kidney injury, associated with deep changes in kidney protein composition. These alterations may act in concert with intrarenal renin-angiotensin system activation and may serve as markers and/or targets to tackle cardiorenal syndrome.